2011
DOI: 10.1063/1.3667205
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in yttrium-doped hafnium oxide

Abstract: Structural incommensurate modulation rule in hexagonal Ba(Ti1-xMx)O3-δ (M = Mn, Fe) multiferroics AIP Advances 2, 042129 (2012) Water assisted gate induced temporal surface charge distribution probed by electrostatic force microscopy J. Appl. Phys. 112, 084329 (2012) Influence of target composition and deposition temperature on the domain structure of BiFeO3 thin films AIP Advances 2, 042104 (2012) Nanodomain structures formation during polarization reversal in uniform electric field in strontium barium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
351
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 584 publications
(381 citation statements)
references
References 33 publications
8
351
2
3
Order By: Relevance
“…Furthermore, ferroelectricity was found in the 9 nm mixed oxide thin film Hf0.5Zr0.5O2 (HZO) 2 deposited on TiN electrodes, although neither the pure HfO2 nor the pure ZrO2 film exhibit ferroelectricity. The existence of a true ferroelectric effect has been confirmed by various experiments such as P-V and C-V measurements 8 as well as retention extrapolated up to 10 years 12 and the occurrence of orthorhombic peaks in XRD measurements 13 . ZrO2 was also studied extensively in the context of functional thin films since its tetragonally stabilized form has a high dielectric constant.…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, ferroelectricity was found in the 9 nm mixed oxide thin film Hf0.5Zr0.5O2 (HZO) 2 deposited on TiN electrodes, although neither the pure HfO2 nor the pure ZrO2 film exhibit ferroelectricity. The existence of a true ferroelectric effect has been confirmed by various experiments such as P-V and C-V measurements 8 as well as retention extrapolated up to 10 years 12 and the occurrence of orthorhombic peaks in XRD measurements 13 . ZrO2 was also studied extensively in the context of functional thin films since its tetragonally stabilized form has a high dielectric constant.…”
Section: Introductionmentioning
confidence: 68%
“…This is consistent with previous results. 1, 8,10,11,15) First, the emergence of the ferroelectric phase in HfO 2 films was discussed on the basis of mechanical stress through the TiN electrodes at the bottom and top of HfO 2 films. 3) Later, it was demonstrated that the top TiN capping layer is not necessary, although it affects the volume fraction of the ferroelectric phase in the film.…”
Section: Resultsmentioning
confidence: 99%
“…1,4,5) The ferroelectricity of HfO 2 films is maximized in ultrathin films of around 10 nm thickness. Crystallization of HfO 2 films begins at low annealing temperatures of around 400°C, 11) and the ferroelectric property is stable after annealing at 1000°C. 2,3) Currently, ultrathin HfO 2 films are attainable by atomic layer deposition (ALD) and are already utilized as the major gate stack material for advanced metal-oxide-semiconductor field-effect transistors (MOSFETs) in largely integrated circuits (LSIs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It believes that the strategy reported here could be extended to a variety of BLSFs oxides for the design of new ferroelectric materials with optical and electric multifunction and this strategy could be applied to the newly discovered promising ferroelectric materials such as hafnium oxide which ferroelectric properties can be controlled by doping rare earth elements. 73 …”
Section: Piezoelectric Propertiesmentioning
confidence: 99%